PERSOALAN PSIKOLOGIS DAN REKONSTRUKSI MITOS DALAM CERITA FANTASTIK PADA KUMPULAN CERPEN BUMI KUNTILANAK KARYA DENNY HERDY - Dheny Jatmiko; Linusia Marsih (Universitas 17 Agustus 1945 Surabaya, 2016)
Abstract. Bumi Kuntilanak is collection of short stories written by two young writers: Denny Herdy and Sandza. This article discusses seven short stories by Denny Herdy of the collection, namely